Gambaran Konsep Diri Pengamen Jalanan - Fitria, Fitria -; Abidin, Muhammad Zainal; Imadduddin, Imadduddin (Jurnal Al-Husna, 2020)
Those who are able to judge themselves as poor or called negative self-concept, will always try to stay away in relationships with their surrounding environment or act aggressively unnaturally but not naturally but can judge themselves well or have a positive self-concept and can overcome their problems. whatever problem it will be able to face and will solve it. Based on preliminary studies and previous research, it was found that self-concept is an important concept for interacting with the environment. Therefore, this study aims to determine how the self-concept image of street residents in the Al-Ayjb Foundation includes internal and external dimensions. This study is a qualitative descriptive study, with 3 subjects aged 17-20 years old. The data method used is the interview method, the method of observation and the method of documentation. The results showed that the self-concept image of the street singers at Al-Ayjb Foundation based on the internal dimension tends towards a positive self-concept because of the three subjects expressing opinions or things that are good or positive about themselves while from the external dimension it tends to negative self-concept.